Multiculturalism and Conflict Reconciliation in the Asia-Pacific
XIV, 237 p.
Keywords: This book is open access under a CC BY license. This edited collection focuses on theories, language and migration in relation to multiculturalism in Japan and the Asia-Pacific. Each chapter aims to provide alternative understandings to current conflicts that have arisen due to immigration and policies related to education, politics, language, work, citizenship and identity.